2001
DOI: 10.1046/j.1365-2141.2001.02977.x
|View full text |Cite
|
Sign up to set email alerts
|

Mast cells express functional CD30 ligand and are the predominant CD30L‐positive cells in Hodgkin's disease

Abstract: Summary. Hodgkin's disease (HD) tumours are characterized by the presence of few tumour cells, the Hodgkin and Reed-Sternberg (HRS) cells, surrounded by a large amount of non-neoplastic cells. The role of this cell infiltrate for the development of HD is not known. CD30, belonging to the tumour necrosis factor receptor superfamily, is highly expressed on HRS cells and believed to be involved in tumourigenesis and tumour progression. Tumour samples from 42 patients were immunohistochemically doublestained for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
2
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(102 citation statements)
references
References 40 publications
2
97
2
1
Order By: Relevance
“…It has recently been shown that mast cells express functional CD30L/CD153 and are the predominant CD30L-positive cells in Hodgkin lymphoma. 44 In addition, functional CD30L has also been demonstrated in almost all mast cells of the HMC-1 mast cell leukemia cell line. 44 Thus, the demonstration of the consistent expression of CD30 in the majority of neoplastic mast cells in aggressive variants of systemic mastocytosis may argue for possible interactions between CD30 and its ligand, CD153, in neoplastic mast cells.…”
Section: Cd30 In Advanced Mastocytosismentioning
confidence: 98%
See 1 more Smart Citation
“…It has recently been shown that mast cells express functional CD30L/CD153 and are the predominant CD30L-positive cells in Hodgkin lymphoma. 44 In addition, functional CD30L has also been demonstrated in almost all mast cells of the HMC-1 mast cell leukemia cell line. 44 Thus, the demonstration of the consistent expression of CD30 in the majority of neoplastic mast cells in aggressive variants of systemic mastocytosis may argue for possible interactions between CD30 and its ligand, CD153, in neoplastic mast cells.…”
Section: Cd30 In Advanced Mastocytosismentioning
confidence: 98%
“…44 In addition, functional CD30L has also been demonstrated in almost all mast cells of the HMC-1 mast cell leukemia cell line. 44 Thus, the demonstration of the consistent expression of CD30 in the majority of neoplastic mast cells in aggressive variants of systemic mastocytosis may argue for possible interactions between CD30 and its ligand, CD153, in neoplastic mast cells. One possibility could be that CD30-CD153 interactions are involved in autocrine growth regulation.…”
Section: Cd30 In Advanced Mastocytosismentioning
confidence: 98%
“…Second, IL-13 may act as a growth factor for certain tumors, promoting tumor expansion (39). In Hodgkin's disease, CD30 ϩ Reed-Sternberg (H/RS) cells are surrounded by nonneoplastic cells, many of which are mast cells expressing CD30L (40). IL-13 production following engagement of CD30 on T cells by CD30L on mast cells could potentially both directly promote growth of certain tumor types and reduce tumor elimination by T cells.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of CD153 (CD30L) was observed on mast cells from patients with Hodgkin's diseases (40), suggesting the contribution of mast cell-derived CD153 to the pathology associated with the disorder. In this study we report for the first time the expression of CD153 on mouse BMCMCs (Fig.…”
Section: Expression Of Members Of the Tnf And Tnfr Families Of Molecumentioning
confidence: 99%